Empowerment Program Based on BASNEF Model and the General Health of Hemodialysis Patients - Mohammad Aghajani; Zahra Saeidnejad; Neda Mirbagher Ajorpaz (Iran University of Medical Sciences, 2020)
Background: Hemodialysis patients encounter various physical, mental, and social health problems. Empowerment programs may facilitate behavioral changes and improve general health. This study aimed to determine the effectiveness of the empowerment program on the general health of hemodialysis patients. Methods: In this clinical trial, 60 patients undergoing hemodialysis were selected from Shahid Beheshti Hospital in Kashan City, Iran. The patients were randomly divided into two groups. In the intervention group, the empowerment program based on the BASNEF (belief, attitude, subjective norm, and enabling factors) model was implemented in 8 sessions. No intervention was performed for the control group. Before and after the intervention, Goldberg's General Health Questionnaire (GHQ) was completed by the two groups and compared. The obtained data were analyzed using the independent-test, paired t-test, and Chi-square test in SPSS V. 13.  Results: A significant decrease in the GHQ scores was observed after the intervention in the intervention group but the difference was not statistically significant between the groups (P=0.2). However, the difference between the scores of GHQ subscales, including "somatic symptoms", "anxiety and insomnia", and "social dysfunction" were significant (P<0.05). The paired t-test results showed significant differences in the mean scores of GHQ subscales in the intervention group before and after the intervention (P<0.05). But these differences were not significant in the control group (P=0.2).  Conclusion: The BASNEF model empowerment was effective on the general health of patients undergoing hemodialysis. Using this program is suggested for these patients.